Light-activatable and hyperthermia-sensitive “all-in-one” theranostics: NIR-II fluorescence imaging and chemo-photothermal therapy of subcutaneous glioblastoma by temperature-sensitive liposome-containing AIEgens and paclitaxel - Du, Lixin; Wang, Pan; Huang, Haiyan; Li, Menglong; Roy, Shubham; Zhang, Yinghe; Guo, Bing (Frontiers in Bioengineering and Biotechnology, 2023)
Nowadays, it is still quite difficult to combat glioblastoma, which is one of the most lethal cancers for human beings. Combinatory therapy, which could not only improve therapeutic efficacy and overcome multiple drug resistance, but also decrease threshold therapeutic drug dosage and minimize side effect, would be an appealing candidate for glioblastoma treatment. Herein, we report fluorescence image in the second near-infrared window (NIR-II)-guided combinatory photothermal and chemo-therapy of glioblastoma with newly formulated nanomedicine termed PATSL. It is composed of temperature sensitive liposome carrier, NIR-II emissive and photothermal aggregation-induced emission (AIE) dyes and as well chemotherapeutic paclitaxel. PATSL shows spherical morphology with diameter around 55 and 85 nm by transmission electron microscopy and laser light scattering, respectively, and zeta potential of -14.83 mV, good stability in both size and photoactivity, strong light absorption with a peak around 770 nm and bright emission from 900 nm to 1200 nm. After 808 nm laser excitation with good spatiotemporal contrability, PATSL emit bright NIR-II fluorescence signals for tumor diagnosis in vivo, exhibit high photothermal conversion efficiency (68.8%) and triggered drug release of paclitaxel under hypothermia, which assists to efficient tumor ablation in vitro and in vivo. This research demonstrates that "all-in-one" theranostics with NIR-II fluorescence image-guided combinatory photothermal and chemotherapeutic therapy is an efficient treatment paradigm for improving prognosis of brain cancers.